Estimation of seasonal stages based on climate parameters measured at the Apacheta micro-basin weather station, Ayacucho Region, 2000 to 2018 - Moncada, Wilmer (2020)
The seasonality of rainfall, maximum and minimum air temperature, relative humidity, wind speed and solar radiation impact the ecological status of the Apacheta micro-basin. The objective is to estimate the seasonal stages from climatic parameters measured at the Apacheta micro-basin weather station, based on the selection of intervals of precipitation values. The rainy season includes the months of January, February, March and December, its precipitation is 145.96 mm with maximum air temperature of 12.3 °C, minimum air temperature of 1.55 °C, relative humidity of 74.04 %, wind speed of 2.6 m/s and solar radiation of 527.13 Ly. The intermediate stage in April, September, October and November, with precipitation of 51.89 mm with maximum air temperature of 13.38 °C, minimum air temperature of -0.2 °C, relative humidity of 69.76 %, wind speed of 2.96 m/s and solar radiation of 552.37 Ly. The dry stage in May, June, July and August, with precipitation of 15.41 mm, maximum air temperature of 12.51 °C, minimum air temperature of -2.4 °C, relative humidity of 67.49 %, wind speed of 3.16 m/s and solar radiation of 463.79 Ly.